Éliminer les frontières : le résumé scientifique dans trois communautés discursives - Rivard, Léonard P.; Diop, Lamine; Nyongwa, Moses (Canadian Journal of Applied Linguistics, 2004)
This exploratory study examined how university students in an organic chemistry course summarised an article from a popular science magazine. Their summaries were compared with those produced by professors of science and French, using various grammatical and discursive measures. The chemistry students and science professors incorporated similar frequencies of a larger number of ideas than did the French professors. They were also more succinct and demonstrated greater fidelity to the original text. Their summaries were shorter, and included less jargon and fewer sentences. They also employed fewer connectors, both in terms of number and variety. Although the students made more errors than the science professors, the two groups were similar in terms of syntactic, lexical and spelling errors. The study also indicated how the students were progressively mastering the linguistic and discourse skills specific to the sciences.